Biomarkers for disease severity in children infected with respiratory syncytial virus: a systematic literature review - Öner, D; Drysdale, SB; McPherson, C; Lin, G-L; Janet, S; Broad, J; Pollard, AJ; Aerssens, J; RESCEU Investigators (Oxford University Press, 2020)
Background Clinical manifestations of respiratory syncytial virus (RSV) infection vary widely from mild, self-limiting illness to severe life-threatening disease. There are gaps in knowledge of biomarkers to objectively define severe disease and predict clinical outcomes.